ANALISIS IMPLEMENTASI KEBIJAKAN RETRIBUSI TERMINAL PANGKAJENE TERHADAP PENINGKATAN PAD KABUPATEN SIDENRENG RAPPANG - Muliani Samiri; Nuraeni Kasman; Dewi A; Nurjannah Nonci; Andi Sinrang (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
Implementation of the Pangkajene Terminal Retribution Policy on the Increase of Pad Sidenreng Rappang Regency. the implementation of the terminal retribution collection policy in Sidenreng Rappang Regency has not been carried out properly, so that the terminal retribution income does not achieve the desired results. This is because there are still people who do not understand the importance of collecting terminal fees so that the implementation of collecting terminal fees in Sidenreng Rappang Regency does not reach the target optimally. The purpose of this study was to analyze the implementation of Perbub policy Number 5 of 2017 in Sidenreng Rappang Regency and also to analyze the increase in acceptance of Terminal Retribution in Sidenreng Rappang Regency. The total population used is 330 people. The sampling technique was carried out by means of a random sampling technique, namely the respondent selection technique was carried out randomly without giving any difference, so that all members of the population could be selected as samples. The formula used to determine the sample in this study was: 5% - 10%, 10 % - 15%, 15% - 20%, then the total population taken according to the formula is 330 X 10% = 33 respondents. The results of the study indicate that the implementation of the Perbub policy Number 5 of 2017 in Sidenreng Rappang Regency is less than optimal, this can be seen from the results of the study which only received 66%, while the acceptance of Terminal Retribution in Sidenreng Rappang Regency was still inadequate, this of course was influenced by the five factors. The retribution indicator, which only gets 61% of the 100% expected results, of course needs to be increased to support local revenue.